Metaphysics : Aristotelian, scholastic, analytic - Novák, Lukáš (Contemporary scholasticism, 2012)
Throughout the greater part of the twentieth century, both in the analytic and continental traditions, metaphysics was deemed to be passé. The last few decades, however, have witnessed a remarkable growth of interest among analytic philosophers in various traditional metaphysical topics, such as modality, truth, causality, etc. which resulted in the emergence of various forms of analytic metaphysics. The new forms of metaphysics differ from its traditional forms mostly in their methodology (we may notice various applications of contemporary formal logical techniques) and in the range of propos.